Suppression of LETM1 inhibits the proliferation and stemness of colorectal cancer cells through reactive oxygen species–induced autophagy. Issue 4 (13th December 2020) - Che, Nan; Yang, Zhaoting; Liu, Xingzhe; Li, Mengxuan; Feng, Ying; Zhang, Chengye; Li, Chao; Cui, Yan; Xuan, Yanhua
Abstract: Leucine zipper‐EF‐hand–containing transmembrane protein 1 (LETM1) is a mitochondrial inner membrane protein that is highly expressed in various cancers. Although LETM1 is known to be associated with poor prognosis in colorectal cancer (CRC), its roles in autophagic cell death in CRC have not been explored. In this study, we examined the mechanisms through which LETM1 mediates autophagy in CRC. Our results showed that LETM1 was highly expressed in CRC tissues and that down‐regulation of LETM1 inhibited cell proliferation and induced S‐phase arrest. LETM1 silencing also suppressed cancer stem cell–like properties and induced autophagy in CRC cells. Additionally, the autophagy inhibitor 3‐methyladenine reversed the inhibitory effects of LETM1 silencing on proliferation and stemness, whereas the autophagy activator rapamycin had the opposite effects. Mechanistically, suppression of LETM1 increased the levels of reactive oxygen species (ROS) and mitochondrial ROS by regulation of SOD2, which in turn activated AMP‐activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR), initiated autophagy, and inhibited proliferation and stemness. Our findings suggest that silencing LETM1 induced autophagy in CRC cells by triggering ROS‐mediated AMPK/mTOR signalling, thus blocking CRC progression, which will enhance our understanding of the molecular mechanism of LETM1 in CRC.